The influence of financial risk, product risk, security risk, and psychological risk on online purchase intention of health products through Tokopedia application - Abidin, Naufaldi; Sari, Astri Yuza (Universitas Negeri Padang, 2025)
This research examines the influencing factors Online Purchase Intention on health products in the Tokopedia application in Padang City, with a focus on roles Financial Risk, Product Risk, Security Risk, Psychological Risk. This research aims to determine the effect Financial Risk, Product Risk, Security Risk, Psychological Risk To Online Purchase Intention. The sample used was 140 respondents. Data is processed using SmartPLS and collected via online questionnaires. The research results show that (1) Financial Risk negative and significant effect on Online Purchase Intention. (2) Product Risk negative and insignificant effect. (3) Security Risk positive and insignificant effect. (4) Psychological Risk negative and significant effect on Online Purchase Intention.